Meta‐analysis of the coral environmental stress response: Acropora corals show opposing responses depending on stress intensity. Issue 15 (29th July 2020) - Dixon, Groves; Abbott, Evelyn; Matz, Mikhail
Abstract: As climate change progresses, reef‐building corals must contend more often with suboptimal conditions, motivating a need to understand coral stress response. Here, we test the hypothesis that there is a stereotyped transcriptional response that corals enact under all stressful conditions, functionally characterized by downregulation of growth, and activation of cell death, response to reactive oxygen species, immunity, and protein folding and degradation. We analyse RNA‐seq and Tag‐Seq data from 14 previously published studies and supplement them with four new experiments involving different stressors, totaling over 600 gene expression profiles from the genus Acropora . Contrary to expectations, we found not one, but two distinct types of response. The type A response was observed under all kinds of high‐intensity stress, was correlated between independent projects and was functionally consistent with the hypothesized stereotyped response. The consistent correlation between projects, irrespective of stress type, supports the type A response as the general coral environmental stress response (ESR), a blanket solution to severely stressful conditions. The distinct type B response was observed under lower intensity stress and was more variable among studies. Unexpectedly, at the level of individual genes and functional categories, the type B response was broadly opposite the type A response. Finally, taking advantage of the breadth of the data set, we present contextual annotations for previously unannotated genes based on consistent stress‐induced differences across independent projects.